Serpine1 Knockdown Enhances MMP Activity after Flexor Tendon Injury in Mice: Implications for Adhesions Therapy - Margaret A. T. Freeberg (Nature Portfolio, 2018)
Abstract Injuries to flexor tendons can be complicated by fibrotic adhesions, which severely impair the function of the hand. Adhesions have been associated with TGF-β1, which causes upregulation of PAI-1, a master suppressor of protease activity, including matrix metalloproteinases (MMP). In the present study, the effects of inhibiting PAI-1 in murine zone II flexor tendon injury were evaluated utilizing knockout (KO) mice and local nanoparticle-mediated siRNA delivery. In the PAI-1 KO murine model, reduced adherence of injured tendon to surrounding subcutaneous tissue and accelerated recovery of normal biomechanical properties compared to wild type controls were observed. Furthermore, MMP activity was significantly increased in the injured tendons of the PAI-1 KO mice, which could explain their reduced adhesions and accelerated remodeling. These data demonstrate that PAI-1 mediates fibrotic adhesions in injured flexor tendons by suppressing MMP activity. In vitro siRNA delivery to silence Serpine1 expression after treatment with TGF-β1 increased MMP activity. Nanoparticle-mediated delivery of siRNA targeting Serpine1 in injured flexor tendons significantly reduced target gene expression and subsequently increased MMP activity. Collectively, the data demonstrate that PAI-1 can be a druggable target for treating adhesions and accelerating the remodeling of flexor tendon injuries.